2008
DOI: 10.1016/j.bpc.2008.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Salts enhance both protein stability and amyloid formation of an immunoglobulin light chain

Abstract: Amyloid fibrils are associated with sulfated glycosaminoglycans in the extracellular matrix. The presence of sulfated glycosaminoglycans is known to promote amyloid formation in vitro and in vivo, with the sulfate groups playing a role in this process. In order to understand the role that sulfate plays in amyloid formation, we have studied the effect of salts from the Hofmeister series on the protein structure, stability and amyloid formation of an amyloidogenic light chain protein, AL-12. We have been able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 29 publications
6
56
0
Order By: Relevance
“…We also used thermal denaturation CD to assess the thermal stability of these proteins. By obtaining full CD scans at 5°C increments, we observed that TREM2 has a denaturation transition at 225 nm, consistent with other Ig domains (Sikkink and Ramirez-Alvarado, 2008), and this wavelength was monitored in subsequent denaturation experiments (Figure 3—figure supplement 1a). WT TREM2 and all the TREM2 variants tested showed reversible thermal denaturation as they reacquired their native spectra rapidly after cooling from 90°C to 20°C, but their ability to refold was ablated in the presence of DTT (not shown).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…We also used thermal denaturation CD to assess the thermal stability of these proteins. By obtaining full CD scans at 5°C increments, we observed that TREM2 has a denaturation transition at 225 nm, consistent with other Ig domains (Sikkink and Ramirez-Alvarado, 2008), and this wavelength was monitored in subsequent denaturation experiments (Figure 3—figure supplement 1a). WT TREM2 and all the TREM2 variants tested showed reversible thermal denaturation as they reacquired their native spectra rapidly after cooling from 90°C to 20°C, but their ability to refold was ablated in the presence of DTT (not shown).…”
Section: Resultssupporting
confidence: 72%
“…For these experiments, we chose to analyze the R47H and R62H mutations, as they represent the most significant TREM2 risk factors identified to date, as well as the T96K mutation, which is a sporadically occurring mutation that is not significantly associated with AD. In order to evaluate whether the point mutations induced conformational changes, we collected CD spectra on the proteins, analyzed for large changes, and compared the ratio in minima at 214 nm (due to β sheets) to minima at 233 nm (due to tryptophans), which are characteristic features of the CD spectra for Ig folds (Sikkink and Ramirez-Alvarado, 2008). We found that R62H and T96K displayed CD spectra similar to WT proteins while, surprisingly, R47H showed a subtle, yet statistically significant difference in the 214 nm/233 nm ratio (Figure 3a and b).…”
Section: Resultsmentioning
confidence: 99%
“…A number of recent studies have supported our observation of accelerated fibril formation in kosmotropic salts using different amyloid forming systems. 32,33 If our observation on chaotropic salt inhibition holds true for other systems, chaotropic salt solutions may potentially serve as a basis for the treatments that would decrease amyloidogenic potential of the prion contaminants and in this way, prevent the spread of prion infections via medical mistreatment.…”
Section: Discussionmentioning
confidence: 93%
“…Protein expression was performed as reported previously (10,34,35). Briefly, all plasmids were transformed into Escherichia coli BL21 (DE3) Gold competent cells (Stratagene, La Jolla, CA), and protein expression was induced with 0.8 mM isopropyl-␤-D-thiogalactopyranoside at an A 600 nm of 0.7.…”
Section: Methodsmentioning
confidence: 99%